A short, structured skills training course for critical care physiotherapists in a lower-middle income country. (2nd September 2018) - Tunpattu, Sanjeewa; Newey, Victoria; Sigera, Chathurani; De Silva, Pubudu; Goonarathna, Amal; Aluthge, Iranga; Thambavita, Pasan; Perera, Rohan; Meegahawatte, Amila; Isaam, Ilhaam; Dondorp, Arjen M; Haniffa, Rashan
ABSTRACT: Objectives : The aim of this article is to describe the delivery and acceptability of a short, structured training course for critical care physiotherapy and its effects on the knowledge and skills of the participants in Sri Lanka, a lower-middle income country. Methods : The two-day program combining short didactic sessions with small group workshops and skills stations was developed and delivered by local facilitators in partnership with an overseas specialist physiotherapist trainer. The impact was assessed using pre/post-course self-assessment, pre/post-course multiple-choice-question (MCQ) papers, and an end-of-course feedback questionnaire. Results : Fifty-six physiotherapists (26% of critical care physiotherapists in Sri Lanka) participated. Overall confidence in common critical care physiotherapy skills improved from 11.6% to 59.2% in pre/post-training self-assessments, respectively. Post-course MCQ scores (mean score = 63.2) and percentage of passes (87.5%) were higher than pre-course scores (mean score = 36.6; percentage of passes = 12.5%). Overall feedback was very positive as 75% of the participants were highly satisfied with the course's contribution to improved critical care knowledge. Conclusions : This short, structured, critical care focused physiotherapy training has potential benefit to participating physiotherapists. Further, it provides an evidence that collaborative program can be planned and conducted successfully in a resource poor setting. This sustainable short course model may be adaptable to other resource-limited settings.